CUSHING’S SYNDROME FROM CONCOMITANT THERAPY OF RITONAVIR AND FLUTICASONE - Engkakul, Pontipa; Bunjoungmanee, Pornumpa; Yodvisitsak, Wiraporn; Tangsathapornpong , Auchara (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE The most common cause of Cushing’s syndrome (CS) is exogenous steroid use. We present a 9-year-old female with CS from a drug interaction between an intranasal steroid (INS) and a protease inhibitor. She was treated for HIV with zidovudine, lamivudine, and lopinavir/ritonavir. At the age of 6.5 years, she had used intranasal fluticasone furoate to control allergic rhinitis. She had poor linear growth and she became extremely short. She has truncal obesity, a moon face, and purplish abdominal striae at the age of nine. The 8 a.m. serum cortisol level was less than 0.05 mcg/dL, with no response to the 1 mcg ACTH stimulation test. Thus, exogenous CS was diagnosed. Ritonavir inhibits the hepatic CYP3A4 isozyme resulting in decreased glucocorticoid metabolism. Interaction between ritonavir and fluticasone was suspected as the cause of CS. After the withdrawal of INS, the clinical features of CS improved. Therefore, children receiving antiretroviral medication should use steroids with caution.